Characterisation, physicochemical and functional properties of protein isolates from Amygdalus pedunculata Pall seeds. (1st May 2020) - Li, Cong; Yang, Juzhuan; Yao, Lu; Qin, Fangling; Hou, Guofeng; Chen, Bang; Jin, Lihua; Deng, Jianjun; Shen, Yehua
Highlights: Physicochemical and functional properties of protein of API were first studied. Nearly 300 proteins were identified by the combination of 2D-PAGE and LC/MS. Protein of Amygdalus pedunculata Pall seeds had good functional properties. The effect of denaturants on the conformation of API was GdnHCl > urea > SDS. Abstract: Amygdalus pedunculata Pall is a kind of desert woody oil plant, and its seeds are high in protein. The protein of Amygdalus pedunculata Pall (API) was identified by SDS-PAGE, 2-DE and MS. More than 300 proteins were identified. The improved solubility, emulsifying properties and foaming properties of API were observed in a pH range of 2.0–12.0 and a sodium chloride concentration of 0–1.0 M. The results showed that API had a good solubility (94.2%), bulk density (0.107 g/mL), oil absorption capacity (3.54 g/g), thermal stability (91.58 °C), emulsifying property (70 m 2 /g) and foaming property (83.7%). The conformation changes of API were studied by fluorescence and differential scanning calorimetry (DSC). The degree of denaturation of denaturants for API was guanidine hydrochloride > urea > SDS. These results showed that API has good processing performance and can be used as a new type of plant protein resource.